Studies on hysteria - "Breurer, Josef." (Middlesex Eng, 1983)
In these studies we can watch some of the major concepts of psychoanalysis being hatched. Such obstacles as amnesia and the patient's unwitting resistance to treatment are encountered; an 'unconscious' mind is reveled; the strength of sexual instincts is underlined; the phenomenon of transference is recognized and the principle of constancy formulated.
Keywords: Psychology